Biossensores contendo acetilcolinesterase de formigas cortadeiras para screening de potenciais inseticidas naturais - Araújo, Sean dos Santos (2024)
Some of the agricultural pests most responsible for damage and losses are leaf-cutting ants (genus Atta and Acromyrmex). This insect causes damage in agricultural and forestry areas, mainly in monocultures, such as Pinus, Eucalyptus, Gmelina and Citrus. The application of chemical compounds such as organophosphates and carbamates to control ants can have a negative impact on the environment and human health. Based on this, in the present work, two electrochemical biosensors based on acetylcholinesterases from leaf-cutting ants were developed to detect potential inhibitors from plant extracts. For the development of the biosensors, the electrodes were screen-printed on polyester foil using carbon and Ag/AgCl-based inks. The modification of the surface of the working electrode was necessary for the immobilization of the enzymes AChE A and AChE B by covalent bonding. The enzymatic activity was detected through the peak current corresponding to the product of the occurrence between AChEs and the substrate acetylthiocholine iodide (ATChI), thiocholine (TCh). After the studies to optimize the conditions for both biosensors, they presented enzymatic activity responses up to the thirteenth day after the immobilization of AChEs on the electrodes. The inhibition studies with organophosphate malathion reached detection limits of 9.1 nmol L-1 for AChE A and 4.7 nmol L-1 for AChE B. Thus, the extracts of Solanum lycocarpum and Ocotea sp. were applied for inhibition studies and provided different inhibitory activity profiles between themselves and for each enzyme. The extract of Solanum lycocarpum obtained 80% inhibition against AChE A, being a promising extract for future studies in the search for natural insecticides for leaf-cutting ants. The developed biosensors are a new tool for screening extracts with potent insecticidal activities.